Employer sanctions, and the welfare of native workers - Oded Stark; Marcin Jakubek (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
We investigate the impact of the imposition of sanctions for employing illegal migrants on the welfare of native workers. Our analysis is based on the premise that in response to such sanctions, managers in a firm may be reassigned from supervision of production to verification of the legality of the firm's workforce. When there is full employment in the host country, a profit-maximizing firm will assign managers to verification if the sanctions are steep enough. This reassignment impedes production efficiency and, consequently, leads to a reduction in the wages of both illegal migrants and native workers, inevitably hurting the latter, who are the intended beneficiaries of the sanctions.
urn:nbn:de:bsz:21-opus-62741
Keywords: D21; I38; J21; J61; K31; L51; 330; Employer sanctions; Illegal migrant workers; Natives' welfare; The formation of public policy; Schwarzarbeit; Migranten; Strafe; Bevölkerung; Wohlfahrtsanalyse; Theorie